PENGARUH MODEL PROJECT BASED LEARNING PADA DIMENSI LULUSAN (P8) TERHADAP HASIL BELAJAR MATERI PERSATUAN DAN KESATUAN - Setiyono, Rahman; Faipri Selegi, Susanti; Gunawan, Hendri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The project based learning model is a project-basedlearning model. The purpose of this study was todetermine the effect of the project based learningmodel on the collaboration dimension on studentlearning outcomes on the subject of unity andoneness. The research method used a quantitativepre-experimental one group pretest-posttest design. This study was conducted at SDN 025 Palembang, with a sample of 29 students of class V.c using a purposive sampling technique. The data were described non-parametrically. The results of the study obtained an Asymp. signature value. (2-tailed) of 0.000 <0.05 and an N-Gain Score of 60%, thus thehypothesis test was accepted and stated that therewas an effect of the Project based learning model onstudent learning outcomes of class V.c at SD Negeri 025 Palembang and was proven to improve studentlearning outcomes.